Networks for homes. - Dutta-Roy, A. (IEEE spectrum)
Networking technologies are starting to invade the ordinary home-to carry, for example, telephone conversations, television, compact disk, digital versatile disk and MP3 music programs, signals from surveillance cameras, commands for controlling appliances and multimedia news from the Internet. To succeed, home networks will have to be based on standard products operable with any of the media just mentioned. These products include transceivers, network interface cards, gateways, small servers, sensors and controllers, plus a widely accepted operating system. For mass market appeal, the networks will have to be inexpensive, easy to install and the software easy to configure and operate. Home owners, after all, cannot afford to hire information technology managers